2021
DOI: 10.1101/2021.07.06.451238
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Outer membrane vesicles derived from Klebsiella pneumoniae are a driving force for horizontal gene transfer

Abstract: Gram-negative bacteria release outer membrane vesicles (OMVs) into the extracellular environment. Recent studies recognized these vesicles as vectors to horizontal gene transfer, however the parameters that mediate OMVs transfer within bacterial communities remain unclear. The present study highlights for the first time the transfer of plasmids containing resistance genes via OMVs derived from Klebsiella pneumoniae ( K. pneumoniae ). This mechanism confers DNA protection and it is plasmid copy number depen… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Several studies have reported that OMVs carrying resistance and virulence genes have the potential of delivering them to other bacteria (Bielaszewska et al., 2020b; Chatterjee et al., 2017; Kolling & Matthews, 1999). Recent report shows that K. pneumoniae can transfer a resistance plasmid to sensitive Enterobacteriaceae through OMVs, and OMVs‐mediated resistance plasmid transfer has high transfer efficiency (Dell'Annunziata et al., 2021). However, K. pneumoniae transfer virulence genes into recipient cells via OMVs, even into carbapenem‐resistant bacteria remain currently unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported that OMVs carrying resistance and virulence genes have the potential of delivering them to other bacteria (Bielaszewska et al., 2020b; Chatterjee et al., 2017; Kolling & Matthews, 1999). Recent report shows that K. pneumoniae can transfer a resistance plasmid to sensitive Enterobacteriaceae through OMVs, and OMVs‐mediated resistance plasmid transfer has high transfer efficiency (Dell'Annunziata et al., 2021). However, K. pneumoniae transfer virulence genes into recipient cells via OMVs, even into carbapenem‐resistant bacteria remain currently unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies, the antimicrobial‐resistance genes located at large plasmids are carried by E. coli‐ derived OMVs, which hold the ability to transfer them into other E. coli strains (Bielaszewska et al., 2020b). K. pneumoniae can produce OMVs, and its OMVs also act as vectors for the transfer of plasmid‐encoded antimicrobial‐resistance genes (Dell'Annunziata et al., 2021). In 2018, scholars propose the emergence of carbapenem‐resistant hypervirulent K. pneumoniae (CR‐hvKp) isolates (Yao et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Exposure of the vesicles to DNase treatment abolished transmission of streptomycin but not penicillin resistance, suggesting that the plasmid DNA, but not the chromosomal DNA, was protected by the MV. Since this discovery, MV‐mediated transfer of many clinically relevant, plasmid‐borne antibiotic resistance genes has been reported for a range of Gram‐negative bacteria 62,64,65 . In one such study, MVs from a carbapenem‐resistant clinical strain of A. baumannii were found to contain the plasmid‐borne bla OXA‐24 gene 64 .…”
Section: Transmission Of Antibiotic Resistance Genesmentioning
confidence: 99%
“…Since this discovery, MV-mediated transfer of many clinically relevant, plasmid-borne antibiotic resistance genes has been reported for a range of Gram-negative bacteria. 62,64,65 In one such study, MVs from a carbapenem-resistant clinical strain of A. baumannii were found to contain the plasmid-borne bla OXA-24 gene. 64 Coincubating these MVs with a carbapenem-susceptible A. baumannii strain was sufficient to produce highly carbapenem-resistant transformants expressing bla OXA-24 .…”
Section: Transmission Of Antibiotic Resistance Genesmentioning
confidence: 99%
“…A. baumannii strain A_115 can transport bla NDM‐1 through OMVs to A. baumannii ATCC 19606 and E. coli JM109 (Chatterjee et al ., 2017). Another example is the OMVs of K. pneumoniae , which transfers plasmids encoding resistance genes to E coli , S. enterica , P. aeruginosa and Burkholderia cepacia (Dell'Annunziata et al ., 2021b). OMVs can reach the gastrointestinal tract, interact with gastrointestinal cells and regulate the host's immune response (Jones et al ., 2020).…”
Section: Wide Spread Of Arb (From Less To More)mentioning
confidence: 99%